Peran Media Dalam Kontruksi Sosial, Politik, Dan Ekonomi Digital - wahyudi, Sophan; Sophan; Arswendi, Riki; Mongkau, Imanuel Ronald David; Satyahadi, Alfred (Universitas Muhammadiyah Magelang, 2026)
This study aims to analyze the role of media in digital social, political, and economic construction through a media political economy perspective. The method used is a Systematic Literature Review (SLR) of 20 reputable scientific articles for the 2020–2025 period selected using PRISMA guidelines. The analysis was conducted qualitatively with a conceptual and thematic approach to identify patterns of production, distribution, and framing of media content. The results show that digital media is no longer neutral but rather functions as a strategic actor that shapes social reality through ideological representation, power relations, and economic interests. In the context of digital politics, media becomes an arena for power contestation influenced by ownership structures, state intervention, and market logic. Meanwhile, in the economic dimension, digital transformation encourages media platformization based on data, algorithms, and monetization of audience attention, which strengthens digital capitalism. The resulting impact is ambivalent, opening up space for public participation while simultaneously triggering disinformation, polarization, and unequal access to information. The novelty of this research lies in the integration of social, political, and economic dimensions within a comprehensive and contextual analytical framework, particularly in understanding the dynamics of digital media in Indonesia. This research provides theoretical contributions to the development of media political economy studies and practical implications for understanding the relationship between media, power, and society in the digital era.